MANAGEMENT OF POST-HARVEST FUNGAL DISEASES ON SAPOTA FRUIT ( ) USING PLANT EXTRACTS MANILKARA ZAPOTA (Journal of Plant Disease Sciences, 2024)
Postharvest fungal diseases pose a significant challenge in preserving the quality and extending the shelf life of sapota (Manilkara zapota) fruit. The current study aimed to characterize and manage postharvest fungal pathogens affecting sapota fruit through the application of different plant extracts. Fungal pathogens were isolated from infected sapota fruit samples collected from various locations. The efficacy of essential oils and aqueous plant extracts derived from various medicinal plants was evaluated against key fungal pathogens using the Poisoned Food Technique. The experimental results revealed that the fruit showed notable infections from different pathogenic fungi like Pestalotiopsissp., Penicilliumcitrinum, Talaromycesverruculosus, Lasiodiplodiapseudotheobromae, Colletotrichum cliviicola, Aspergillus niger, Dothideomycetesorghinum, and Pestalotiopsismangiferaamong others. All tested plant extracts and essential oils exhibited inhibitory effects against the fungal pathogens, with significant reductions in fungal mycelial growth observed. Notably, essential oils of Syzygium aromaticum and Mentha piperita demonstrated high efficacy, achieving 100% inhibition against several fungal pathogens even at low concentrations. Conversely, Punica granatum L. exhibited lower efficacy, particularly against Penicillium citrinum. Molecular identification of the pathogens was also conducted, and the accession numbers were submitted to NCBI. This study demonstrated the potential of plant-based extracts, particularly essential oils, as effective alternatives for managing postharvest fungal diseases in sapota fruit.
Keywords: Essential oil; characterization; post harvest; Sapota; Poisoned food technique